Dynamic Website of Gresik City'S Halal Life Style as the Implementation of Online Branding in a Smart City - Tyas Ajeng Nastiti; Alfina Alfina; Nova Ridho Sisprasojo (International Telecommunications Society (ITS), 2018)
Understanding potential of a city can be defined by some indicators. One of them is by identifying six indicators that well known as Nation Brand Hexagon. Nation Brand Hexagon are: People, Tourism, Exports, Governance, Investment and Immigration, and Culture and Heritage. By understanding and identifying those six indicators, a city can be more understand about its potential and developing it into City Branding activity. City Branding is the use of marketing techniques to give a City a unique identity in the minds of citizens, visitors, companies and investors. The needs of City Branding for a certain city or area is currently being a marketing strategy that often work effectively. The result of an effective City Branding is particularly giving a profit and a significant increase of economy value. Gresik City (older spelling: Grissee); (Javanese: Nggersik) is a regency within East Java Province of Indonesia. It includes the offshore Bawean Island, some 125 km to the north of Java and Madura. The regency's administrative center is the town of Gresik, about 25 km to the northwest of Surabaya City. Gresik City is known as a city which having a charm of Moslem religion tourism. A lot of activities based on Moslem religion in the city. The total population of 1,2 million people made Gresik City as plural cultures and also producing some products that contain high spiritual value. Beside, Gresik City is also being a city who has many industrial activities. In 2010, Gresik City's income is being the most higher in East Java. Even, the average labour's income in Gresik City is also most higher than other cities in East Java. In 2017, have been done the identification of Nation Brand Hexagon against GresikCity. As for the method that been done is through the Observations, Focus Group Discussion, as well as In-depth Interviews. Through the method of Focus Group Discussion that bring representatives of businessmen/Artists, Government, Academia, and Communities; formulated a mapping of Halal Activity in Gresik as Halal Activity octagon or 8 activities of Halal in Gresik which include : Culinary, Religion Tourism, Art, Fashion, Product and Service, Movement, Education, and Culture. As the continuity of City Branding activity in Gresik, Halal Activity octagon is being core of communication that aimed at outlining potential of Gresik City. City Branding strategy nowadays is not only a forming of City's identity but also representing the identity of digital media that contain a lot of human interaction. By using the technology and internet access, it is possible to build an dynamic website that contain Halal Activity Octagon's information, including: research, text, documentation, people who involve, etc. Dynamic website is a platform that make a possibility of two way interaction between both website's maker and user; or user and user. The function of the website is not only as the center of information about the City, but also as the promotional tools and media, marketing tools and media, and digital data of the City. By having a dynamic website, it will be easier to do some measurement about the city, such as: about satisfying, suggestion, and also the value of economy by numbers and data. In this particular research, will be done some analysis about the effectivity of mapping's projection of Gresik City's Halal Activity based on dynamic Website according to answer: the society's need and want, effective marketing, and access. The result of research is an integrated system about City Branding activity based on dynamic website that can be mapped from upstream to downstream. Moreover, this research also wished to create an innovation regarding of center of information about City's potential that can be the open bank data and can be accessed by anyone without any time and distance limitation.
Keywords: 330; Branding; Gresik; Dynamic Website; Smart City